The Protective Effect of Polyphenols for Colorectal Cancer - Ding, Sujuan; Xu, Sheng; Fang, Jun; Jiang, Hongmei (Frontiers in Immunology, 2020)
Colorectal cancer (CRC) is one of the most prevalent cancers that threaten people in many countries. It is a multi-factorial chronic disease caused by a combination of genetic and environmental factors, but it is mainly related to lifestyle factors, including diet. Plentiful plant foods and beverages are abundant in polyphenols with antioxidant, anti-atherosclerotic, anti-inflammatory, and anticancer properties. These compounds participate in host nutrition and disease pathology regulation in different ways. Polyphenolic compounds have been used to prevent and inhibit the development and prognosis of cancer, and examples include green tea polyphenol (−)-epigallocatechin-3-O-gallate (EGCG), curcumin, and resveratrol. Of course, there are more known and unknown polyphenol compounds that need to be further explored for their anticancer properties. This article focuses on the fact that polyphenols affect the progression of CRC by controlling intestinal inflammation, epigenetics, and the intestinal microbe in the aspects of prevention, treatment, and prognosis.